Proving Medical Negligence in Nigeria: A Narrative Review of the Roles of Tribunals, Regulatory Bodies and Councils - , Maxwell Chibuike Opara (Archives of Current Research International, 2025)
This paper examined the roles of tribunal systems, regulatory bodies, and councils in proving medical negligence under Nigerian law. Medical negligence, a significant issue within the Nigerian healthcare system, involves the breach of professional duty resulting in patient harm. In Nigeria, medicolegal negligence remains a growing concern due to inadequate healthcare regulation, limited awareness of patients' rights, and insufficient enforcement mechanisms. The lack of comprehensive legal frameworks and the complexity of judicial processes have further compounded the difficulty in seeking redress for medical negligence cases. The paper focused on disciplinary tribunals, including the Medical and Dental Practitioners Disciplinary Tribunal and counterparts for pharmacists, medical laboratory scientists, nurses, and radiographers. These tribunals serve as quasi-judicial mechanisms to address professional misconduct. Additionally, regulatory bodies such as the Medical and Dental Council of Nigeria (MDCN), National Health Insurance Scheme (NHIS), and Consumer Protection Council (CPC) are evaluated for their roles in overseeing professional conduct and addressing grievances. The paper highlighted critical challenges, including complex evidentiary requirements, procedural inefficiencies, and overlapping jurisdictions among regulatory entities. Through an in-depth analysis, the paper identified gaps in the current framework that hinder accountability and justice in medical negligence cases. It also explored interagency coordination and proposes legal, procedural, and institutional reforms to enhance efficiency and public trust. By addressing these challenges, the paper contributed to developing a robust legal and institutional framework that safeguards the rights of patients and healthcare providers. It underscored the need for a holistic approach, emphasizing collaboration among stakeholders, increased public awareness, and enhanced procedural mechanisms. The findings aim to strengthen accountability in the Nigerian healthcare system, ensuring justice for victims of medical negligence and fostering professional integrity across the sector.